Mendengarkan dan berbicara untuk berkomunikasi: apa yang guru lakukan dan siswa pelajari dari penilaian kelas - Agus Syahrani; Dedi Ari Asfar; Indra Perdana; Petrus Jacob Pattiasana; Bernadetha Nadeak (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
Choosing the right learning media during the Covid-19 pandemic is very important. Students are helped in understanding the learning material delivered with learning media, even though they are studying at home. The purpose of this study is to find out how Edmodo as a medium is used in teaching and learning activities. This research is a research that uses a qualitative approach and uses a phenomenological method to students and teachers. The conclusion obtained in this study is that the communication that occurs between teachers and students in Edmodo takes place effectively through the delivery of material that is easily understood by students.